Application of Organic Fertilizer Enriched Microbia and Biochar in Various Land Management Systems on Total N, Available P, and Available K in Pineapple Plantations - Winih sekaringtyas ramadhani (JOURNAL OF TROPICAL SOILS, 2026)
The decline in pineapple production in Lampung is closely related to soil degradation. The purpose of this study was to study the soil management system and the effects of soil management and organic fertilizer application, influenced by microbes and biochar, on the availability of nitrogen, phosphorus, and potassium nutrients in the soil in pineapple plantations. The study was conducted at PT Great Giant Pineapple (GGP), and soil analysis was conducted at PT GGP's R&D center. The study used a split plot design with 8 treatments and 3 replications. The main plot consisted of the T1 soil management system (plough the land to a depth of 30 cm + chop the pineapple litter 1 time and T2 (plough the land to a depth of 40 cm + chop pineapple litter 2 times. Subplots consist of organic fertilizer influenced by microbes and biochar P1(GGP compost 50 tons ha-1), P2 (GGP compost 40 tons ha-1+biochar 10 tons ha-1), P3 (GGP premium compost 50 tons ha-1), and P4 (GGP premium compost 50 tons ha-1+LOB microbes 40 L ha-1). The results of the study showed that the T treatment P1 increased the total N content of the soil in plants aged 6 MAP to 9 MAP by 0.03%, but was not significant at 3 and 6 MAP. Treatment T1P1 increasing soil available P from 3 MAP to 6 MAP 23.77 ppm. Treatment T1P1 and T2P3 increased soil available K from 3 MAP to 6 MAP by 19.77 ppm and 11.06 ppm, respectively. There was no interaction between T1P1 in increasing soil nutrients. However, there is an interaction between T1P1 in increasing the total N, available P, and available K of the soil. The correlation test showed a positive correlation between pH and available K in the 3rd MAP observation, organic C with total N in the 6th MAP observation, and a negative correlation between organic C and available P in the 9th MAP observation. The implementation of T1P1 addition of biochar contained in compost 50 GGP ton ha-1 with 30 cm tillage and 1x shredding of plant litter increases soil N, P, and K.